Terapi Kognitif Behavior dengan Teknik Manajemen Diri untuk Menangani Kedisiplinan Belajar Siswa SMP Islam Tanwirul Afkar Sidoarjo - Shofi, Nurul Fahimatus; Rofiq, Arif Ainur (Proceedings of International Conference on Da'wa and Communication, 2019)
This research focuses on; (1) behavior cognitive therapy process with self-management techniques in dealing with the discipline of learning of an Islamic middle school student at Tanwirul Afkar Sidoarjo. (2) the final results of the behavior cognitive therapy process with self-management techniques in managing discipline learning of a Tanwirul Afkar Sidoarjo Islamic middle school student.In answering these problems, researchers used qualitative research methods with descriptive case study analysis in which data collection was carried out through observation, interviews and documentation presented in the data presentation and descriptive analysis chapters by comparing before and after the therapy process. In analyzing the process of self-management techniques to improve student learning discipline used is the form of observations and interviews that are presented in the chapter on data presentation and data analysis. In this study was found that the process of self-management techniques to improve student learning discipline through several stages, namely: 1. Making self-monitoring with counselees; 2. Giving rewards if the counselee has reached the target; 3. Making a contract or agreement by looking at the consequences or goals that the counselee wants; 4. Mastering of stimuli. The final results in this study are quite successful because they can full fill four indicators of success. These results can be seen through changes in the counselee towards the better and can improve the discipline of learning.